MICROFILARIA IN PERICARDIAL EFFUSION COEXISTING WITH SPINDLE CELL THYMOMA-A RARE CASE REPORT - Permi, Harish S; N., Samaga B; K., Subramanyam; K., Jayaprakash Shetty; S., Teerthanath; Baikunje, Vidya; Ninan, Kurian (Journal of Health and Allied Sciences NU, 2011)
Lymphatic filariasis is common in tropical countries and is endemic in South India. Filariasis presenting with pericardial effusion is rare, coexisting with spindle cell thymoma is still very rare. We report a case of a 53-year-old male who was admitted to cardiac intensive care unit with severe breathless since two days. Cardiac Echocardiogram showed massive pericardial effusion with cardiac tamponade and large anterior mediastinal mass. Pericardial fluid aspiration drained 1.5 litres of hemorrhagic fluid. Cytology examination revealed microfilaria of Wutchereria bancrofti. FNAC and trucut biopsy from anterior mediastinal mass showed features of spindle cell thymoma. He was treated with diethyl carbamazine thrice daily for one month. He refused for excision of thymoma. This case report is a rare coexistence of microfilaria in pericardial effusion with spindle cell thymoma. We stress the need to consider filariasis as differential diagnosis in the evaluation of hemorrhagic pericardial effusion especially in endemic areas.
Keywords: Pericardial effusion; microfilaria; spindle cell thymoma